Short hospitalization after caesarean delivery: effects on maternal pain and stress at discharge. (2nd September 2018) - Zanardo, Vincenzo; Giliberti, Lara; Volpe, Francesca; Simbi, Alphonse; Guerrini, Pietro; Parotto, Matteo; Straface, Gianluca
Abstract: Purpose: To characterize predischarge maternal pain and stress after caesarean delivery and short hospitalization. Materials and methods: This is a descriptive study with 60 women in the postoperative period of caesarean section and 60 control women after vaginal delivery. Pain and stress were measured by McGill Pain Questionnaire (MGPQ) and by the Stress Measure (Psychological Stress Measure (PSM)), respectively, at mother–infant dyad discharge, scheduled at 36 hours after delivery. Results: Caesarean section was the delivery modality with the highest MGPQ pain and sensorial, evaluative and mixed pain descriptive categories scores. The pain location involved lower abdomen, with associated localizations at back, breast and shoulders. Conversely, vaginal delivery was the delivery modality with the highest stress scores. Conclusion: This study provides important information on the quality of care implications of early discharge practices in puerperae after caesarean delivery, a critical time characterized by qualitatively and quantitatively high pain and stress.